2021
DOI: 10.1186/s43141-021-00119-0
|View full text |Cite
|
Sign up to set email alerts
|

Phytoassisted synthesis of magnesium oxide nanoparticles from Pterocarpus marsupium rox.b heartwood extract and its biomedical applications

Abstract: Background Unlike chemical techniques, the combination of metal oxide nanoparticles utilizing plant concentrate is a promising choice. The purpose of this work was to synthesize magnesium oxide nanoparticles (MgO-NPs) utilizing heartwood aqueous extract of Pterocarpus marsupium. The heartwood extract of Pterocarpus marsupium is rich in polyphenolic compounds and flavonoids that can be used as a green source for large-scale, simple, and eco-friendly production of MgO-NPs. The phytoassisted synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(40 citation statements)
references
References 82 publications
3
37
0
Order By: Relevance
“…The quantitative analysis revealed that the weight percentages of Mg and O ion in the sample were 54.1 and 20.6%, respectively, whereas the atomic percentages were 50.3% and 17.1%, respectively ( Figure 4A ). Similarly, the EDX profile of MgO-NPs fabricated by the Pterocarpus marsupium aqueous extract showed two peaks at 0.5 and 1.5 KeV for O and Mg ions with weight percentages of 69.3 and 30.6%, respectively ( Ammulu et al, 2021 ). The presence of C indicates the bounding of algal metabolites to the MgO-NPs surface.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative analysis revealed that the weight percentages of Mg and O ion in the sample were 54.1 and 20.6%, respectively, whereas the atomic percentages were 50.3% and 17.1%, respectively ( Figure 4A ). Similarly, the EDX profile of MgO-NPs fabricated by the Pterocarpus marsupium aqueous extract showed two peaks at 0.5 and 1.5 KeV for O and Mg ions with weight percentages of 69.3 and 30.6%, respectively ( Ammulu et al, 2021 ). The presence of C indicates the bounding of algal metabolites to the MgO-NPs surface.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that MgO-NPs can be used in novel applications including the removal of toxic waste, catalysis, antimicrobial property, refractory materials and wastewater treatment, ceramics, heavy fuel oils, enhancement of the potential of antioxidant and substrate in ferroelectric thin films, biomedical fields, sensing, adsorbents, lithium batteries, and agriculture sectors [ 18 , 23 , 24 , 25 ]. MgO-NPs are characterized by long-lasting antimicrobial activity, and this phenomenon can be attributed to its ability to tolerate high temperatures and low volatility [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they can be used for numerous biological purposes, such as antibiofilm, antifungal, antibacterial, antiviral, antitumor, anticancer, biosensors, heartburn treatments, molecular signaling, bone regeneration, to lower the complications of magnesium shortage, and as additives to killing food-borne pathogens [ 27 , 28 , 29 ]. MgO-NPs are characterized by low volatility and tolerate high-temperatures, so they can be used as an antimicrobial agent with long-term effects, and interestingly, are proven as a safe nano-compound by the FDA [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%